Studies on the seasonal incidence of sugarcane internode borer, Chilo saccariphagus indicus (kapur) in Tamil Nadu, India - V. Selvanarayanan, M. Thirumalai, R. Seenivasagan (Recent Research in Science and Technology, 2009)
Internode borer (INB), Chilo saccariphagus indicus (Kapur) (Lepidoptera: Pyraustidae) is an important pest on sugarcane which inflicts yield loss of about than 45 per cent. Pest surveillance and forecasting is one of the important prerequisite tools in managing such pests. Hence, an attempt was made to study the seasonal incidence of the INB during 2007 and 2008 at Nellikuppam, Tamil Nadu, India. The study revealed that the peak incidence of INB was observed during June-July, which declined thereafter. Higher temperature and deficit or failure of rainfall during March –May are considered as the favourable factors for the rise in the incidence of INB.